Case report: Endoluminal removal of a retrievable conical inferior vena cava filter with a ruptured retraction hook attached to the wall - Tian, Xuan; Liu, Jianlong; Li, Jinyong; Liu, Xiao (Frontiers in Surgery, 2022)
We reported a case who underwent endoluminal removal of a conical retrievable filter with a ruptured retraction hook that was attached to the wall. A 21-year-old woman with an indwelling Celect (Cook) filter for 1522 days requested for removal. The preoperative ultrasound and CT examinations showed that the filter was inclined, the retraction hook was attached to the inferior vena cava wall, and one pedicle of the filter was broken. The inferior vena cava was unobstructed, no thrombus was found, and an old superficial femoral vein thrombosis was seen in the right lower extremity. The filter retrieval set (Gunther Tulip, Cook) failed to capture the retraction hook. Using the pigtail catheter and loach guide wire with partly removed catheter tip, we applied modified loop-snare technique to successfully cut the proliferative tissue near the tip of the retraction hook, by which the retraction hook re-entered the inferior vena cava, the snare successfully captured the retraction hook and removed the filter, but the broken pedicle remained in the inferior vena cava. We used forceps to capture and pull the broken pedicle to the distal end. The inferior vena cava was unobstructed, no contrast agent spillage and residual were found, and no symptomatic pulmonary embolism was seen. It is very rare that simultaneous occurrence of oblique adherence and fracture is seen on the same filter, however, using the modified loop-snare technique and biopsy forceps technique, the filter and broken pedicle can be removed, which could be a practical auxiliary technique in clinical practice.